Influence of interacting heavy nuclei mass asymmetry on capture cross-section in fusion reactions - Anokhin, R.A.; Pavlii, K.V. (Вопросы атомной науки и техники, 2013)
The effect of beam and target isotope configuration on the capture cross-section is considered using dynamic-statistical description of the first stage of heavy nuclei fusion reactions. It demonstrates that the isotopic configuration of heavy nucleus renders insignificant effect on the capture cross-section. Cross-section decreases by decreasing mass asymmetry due to the change of light nuclei isotope configuration. The capture cross-section increases by increasing charge asymmetry for constant number of nucleons in the compound nucleus. For odd-odd interacting nuclei capture cross-section is from 1.5 to 6 times greater than for even-even nuclei in the same value of protons and neutrons in the compound nucleus.